Solar energetic electron event characteristics as inferred from spacecraft and ground-based observations - Yli-Laurila, Aleksi (My University, 2024)
Massive eruptions of energy and particles from the surface of the Sun are obvious signs that the star is active. Forecasting these eruptions, however, is very difficult but of interest because of the damage that high energy particles can do to spacecraft, astronauts as well as equipment on the surface of Earth. The Sun is continuously monitored with, e.g., white-light imaging instruments such as LASCO on-board SOHO, and ground-based radio frequency instruments like the telescopes in the RTSN network. This thesis is a statistical study of solar energetic electron events, observed mainly by Solar Orbiter, combined with white-light observations of coronal mass ejections (CMEs) and ground-based observations of solar radio bursts. Solar radio bursts are classified into different types, such as type II and III bursts. They are bursts of electromagnetic radiation in the radio domain produced by electrons travelling in the solar atmosphere. The main science question is differentiating the acceleration mechanisms of solar energetic electrons (SEEs), namely, which electrons are accelerated in the solar flare and which ones in a CME-driven shock. Solar flares are quick releases of energy and particles from the surface of the Sun, that can be seen as bright flashes of light. CMEs are large ejections of particles and magnetic flux from the Sun. They are often associated with solar flares and sometimes drive shock waves. Results of the thesis find confirmation of the so-called big flare syndrome – the observation that intense flares are associated with bigger events where phenomena such as fast CMEs and radio bursts appear more frequently. Results of the analysis point at the importance of shocks in producing the most energetic electron events. Findings with elemental abundances suggest that they are not reliable indicators of whether one is observing only flare accelerated particles. Further, this finding hints in the direction of re-acceleration of particles in shocks, as opposed to events where a shock is the only source of acceleration. Findings with spectral indices of the events are in agreement with CME-driven shocks accelerating electrons to flatter spectra. Results also include a statistically significantly harder spectral index for those events with an associated type II burst compared to those without one, with a cut-off value of -4.
Keywords: solar radio bursts, solar energetic electrons, solar flares, coronal mass ejections